APPLICATION OF SODIUM SELENITE IN THE CULTIVATION OF WHITE LUPINE (LUPINUS ALBUS L.) - Seregina, Inga; Belopukhov, Sergey; Vigilyansky, Yuri; Verkhoturov, Vasilij (Journal of Agricultural Sciences (Belgrade), 2023)
In field research it was studied the influence of different methods of application of sodium Selenite on the nutritional value of white lupine varieties Degas. The greatest effect on the content of raw protein was obtained by spraying vegetating plants before the beginning of the flowering phase. In this variant, class 1 grain was obtained while meeting other requirements of the feed Lupin quality standard. The use of selenium contributed to the increase in collection of crude protein with the harvest of the aboveground mass of plants because of stimulation of the processes of nitrogen in plants and its redistribution from vegetative organs to generative organs and promotes the synthesis of protein compounds in the grain of lupin.
Keywords: white Lupin; sodium Selenite; methods of application; spraying; content of raw protein